2021
DOI: 10.14416/j.asep.2021.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Application of Statistical Solvent Mixture Design in Optimizing the Solid-Liquid Extraction of Phenolic Compounds from Mango Seed Kernels

Abstract: Mango seed kernel (MSK) is a waste material of the mango processing industry and is reported to significantly contain phenolic compounds with anti-oxidative properties. In this work, these compounds are isolated via solid-liquid extraction (SLE) in which solvent mixture design approach was used to evaluate the optimal quaternary solvent ratio in relation to the phenolics content of extracts from MSK. The quaternary solvent is composed of ethanol (E), methanol (M), acetone (A), and water (W). The extraction pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…It is noteworthy that methanol was reported in several studies to be effective for extracting low molecular weight compounds, while aqueous acetone is effective for extracting higher molecular weight compounds. 17,30 This agrees with our results since phenylpropionamides, the abundant compounds in hemp seeds, have a high molecular weight.…”
Section: Solvent Effect On the Phenolic Prolesupporting
confidence: 92%
See 1 more Smart Citation
“…It is noteworthy that methanol was reported in several studies to be effective for extracting low molecular weight compounds, while aqueous acetone is effective for extracting higher molecular weight compounds. 17,30 This agrees with our results since phenylpropionamides, the abundant compounds in hemp seeds, have a high molecular weight.…”
Section: Solvent Effect On the Phenolic Prolesupporting
confidence: 92%
“…19,21 This can be explained by the ability of water to swell the cells and disintegrate the walls, enhancing the intracellular penetration of organic solvents. 30 Furthermore, some phenolic compounds are oen conjugated with other molecules, such as polysaccharides and proteins, easily dissolved in water. 21 Also, some physical characteristics of solvents, such as density and viscosity, could massively impact their extraction capacities.…”
Section: Solvent Effect On Tpcmentioning
confidence: 99%
“…For this reason, it is important to study the effect that the extraction conditions have not only on the quantity of extracted phenolic compounds, but also in their bioactivity. In the particular case of the solvents used in the maceration, Cabajar et al [46] reported that, the use of a mixture of ethanol, methanol, acetone and water (3: 3: 3: 1), resulted in a higher extraction yield and a higher biological activity of extracts from mango kernel [46].…”
Section: Solid-liquid Extractionmentioning
confidence: 99%
“…The maximum solubility and desorption equilibrium for gallic acid extraction were achieved at a temperature of 40°C, resulting in a yield of 5.64 ± 0.04 mg/g. 35 to 45°C was reported to be an efficient temperature range to extract phenolic compounds from mango waste (Cabajar et al., 2021 ; Kaur et al., 2022 ). Higher temperatures can improve the yield of plant extracts by increasing the permeability of cell walls and reducing solvent viscosity.…”
Section: Resultsmentioning
confidence: 99%
“…( 2020 ) investigated the effect of solvent mixtures (methanol:acetone:water) along with ultrasound amplitude on the yield of phenolic compounds from MSK via UAE and reported the extraction yield of phenolics as 71.35 mg GAE/g. Furthermore, a quaternary solvent system to extract phenolics from MSK via solid–liquid extraction was reported and concluded that ethanol, methanol, acetone, and water (3:3:3:1) can efficiently extract up to 78.24 mg/g of phenolics (Cabajar et al., 2021 ). The variation in the reported phenolic contents may be attributed to factors such as the type of plant, location of cultivation, extraction process, and the solvent utilized for extraction (Abdalla et al., 2007 ; Dorta et al., 2013 ; Soong & Barlow, 2006 ).…”
Section: Introductionmentioning
confidence: 99%